Aquaporin-4 Dysregulation in a Controlled Cortical Impact Injury Model of Posttraumatic Epilepsy. (21st January 2020) - Szu, Jenny I.; Chaturvedi, Som; Patel, Dillon D.; Binder, Devin K.
Highlights: Traumatic brain injury (TBI) in the frontal cortex can lead to spontaneous recurrent seizures in the hippocampus. Aquaporin-4 (AQP4), a key epileptogenic astrocyte channel, is increased in mice that developed posttraumatic epilepsy (PTE). AQP4 is mislocalized at early time points after TBI, possibly contributing to chronic posttraumatic epileptogenesis. Abstract: Posttraumatic epilepsy (PTE) is a long-term negative consequence of traumatic brain injury (TBI) in which recurrent spontaneous seizures occur after the initial head injury. PTE develops over an undefined period during which circuitry reorganization in the brain causes permanent hyperexcitability. The pathophysiology by which trauma leads to spontaneous seizures is unknown and clinically relevant models of PTE are key to understanding the molecular and cellular mechanisms underlying the development of PTE. In the present study, we used the controlled-cortical impact (CCI) injury model of TBI to induce PTE in mice and to characterize changes in aquaporin-4 (AQP4) expression. A moderate-severe TBI was induced in the right frontal cortex and video-electroencephalographic (vEEG) recordings were performed in the ipsilateral hippocampus to monitor for spontaneous seizures at 14, 30, 60, and 90 days post injury (dpi). The percentage of mice that developed PTE were 13%, 20%, 27%, and 14% at 14, 30, 60, and 90 dpi, respectively. We found a significant increase in AQP4 in the ipsilateral frontal cortex and hippocampus of mice that developed PTE compared to those that did not develop PTE. Interestingly, AQP4 was found to be mislocalized away from the perivascular endfeet and towards the neuropil in mice that developed PTE. Here, we report for the first time, AQP4 dysregulation in a model of PTE which may carry significant implications for epileptogenesis after TBI.